TEACHING AND LEARNING IN RURAL SOCIETIES: PROBLEMS AND STRATEGIES FOR IMPROVEMENT - Mahuta, Muhammad G.; Inuwa, Awwalu Muhammad (Sokoto Educational Review, 2020)
Teaching and learning are socially related concepts, whose fundamental aims are for behavioural changes, acquisition of skills as well as the improvement of socio-economic and political activities. The aims of teaching and learning are the same, whether in the rural or urban societies. This paper examines the nature of teaching and learning in the context of rural societies, the problems associated with teaching and learning in rural societies as well as the strategies that could be taken to improve the situation. The concepts of teaching, learning and rural societies were delineated, which was followed by a theoretical framework, with a view to giving the paper a sociological focus. The problems and strategies for improvement were examined while taking into cognizance the situation or characteristics of teaching and learning in rural societies, which are known to be lack of or inadequate socio-economic facilities, teaching and learning materials and poor school climate and absence of role models. One of the major recommendations of this paper is that, the provision of education facilities to both rural and urban people should be on equal footing, because both communities are using one curriculum under one National Policy on Education. This is to ensure equal quality of educational standard.